PENGARUH MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) TERHADAP KEMAMPUAN MENULIS PUISI PADA SISWA KELAS VIII MTsN 1 MEDAN - Ananda, Dwi; Hutagalung, Trisnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the CORE (Connecting, Organizing, Reflecting, Extending) learning model on the poetry writing ability of eighth grade students of MTsN 1 Medan. The research method used is quantitative with an experimental approach using a two-group posttest only control design. The research sample was determined through a simple random sampling technique, namely class VIII-D as the experimental class and VIII-F as the control class. Data collection techniques were carried out through a poetry writing test. The results showed that the average score of students in the experimental class was 80.05 (good category), while the control class was 64.62 (poor category). Hypothesis testing using a t-test showed a significance value of 0.000 (<0.05), so there was a significant difference between the two classes. Thus, it can be concluded that the CORE learning model has a significant influence on improving students' poetry writing abilitiesKeywords: Implementation of the Deep Dialogue Critical Thinking Learning Model, Fictional Works, Short Story Review Texts.